Thriving among international students in the U.S. during the Trump presidency - Jones, Alexander; Kim, Young K.; Schreiner, Laurie A.; Koo, Katie. K (Journal of International Students, 2023)
International students are critical for a flourishing U.S. higher education landscape (Younger, 2018). During the Trump presidency, however, these students faced significant cultural, economic, and social challenges (Peters & Anderson, 2021). To better understand international students’ success, this study sought to identify pathways to their thriving. Thriving derives from positive psychology and views student success as an appreciative, holistic enterprise (Schreiner, 2016). We investigated whether college experiences and environments contributed to the variation in international student thriving at U.S. universities. Utilizing structural equation modeling, we specified a statistical model that explained nearly 70% of the variation in this population’s thriving. Psychological Sense of Community, Institutional Integrity, student-faculty interaction, and spirituality were the most significant contributors to the variation in international student thriving. The implications of these results include a focus on culturally responsive pedagogy and redefining acculturation to include the university’s responsibility to create environments where international students can thrive.